Numerical Interpretations of Creep Buckling Behavior of Columns - Walczak, J.; Zacharzewski, J. (Engineering Transactions, 1982)
Analysis of creep buckling columns is described and evaluated. Two different approaches are presented: 1) a numerical solution of a differential equation for the large deflection analysis; 2) the finite element method for material and geometric nonlinearities. An approximate energy method is also employed to evaluate the critical time. The discussion presented underlines the basic divergences in existing solution.